2020
DOI: 10.1111/1759-7714.13626
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate gene expression‐based survival predictor model in esophageal adenocarcinoma

Abstract: Background: Despite the recent development of molecular-targeted treatment and immunotherapy, survival of patients with esophageal adenocarcinoma (EAC) with poor prognosis is still poor due to lack of an effective biomarker. In this study, we aimed to explore the ceRNA and construct a multivariate gene expression predictor model using data from The Cancer Genome Atlas (TCGA) to predict the prognosis of EAC patients. Methods: We conducted differential expression analysis using mRNA, miRNA and lncRNA transciptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…ITPR1 was found downregulated in the esophageal adenocarcinoma (EAC) tissues compared with the normal [ 39 ]. Basing the TCGA database, Zhao et al found that ITPR1 could be a potential biomarker for esophageal adenocarcinoma [ 40 ]. ITPR1 may also involve in head and neck squamous cell carcinoma cancer genetics.…”
Section: Discussionmentioning
confidence: 99%
“…ITPR1 was found downregulated in the esophageal adenocarcinoma (EAC) tissues compared with the normal [ 39 ]. Basing the TCGA database, Zhao et al found that ITPR1 could be a potential biomarker for esophageal adenocarcinoma [ 40 ]. ITPR1 may also involve in head and neck squamous cell carcinoma cancer genetics.…”
Section: Discussionmentioning
confidence: 99%
“…ITPR1 (inositol 1,4,5‐trisphosphate receptor 1) is a ligand‐gated ion channel in regulating calcium release from endoplasmic reticulum and acts as a autophagy sensor 42 . ITPR1 down‐regulation is observed in esophageal adenocarcinoma and has been recognized as a potential biomarker of prognosis in esophageal adenocarcinoma 43,44 . MAP1LC3C (microtubule‐associated protein 1 light chain 3 gamma), a critical structural protein in autophagosome membrane, has been reported to be an independent prognostic biomarker in colorectal cancer 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…as a potential biomarker of prognosis in esophageal adenocarcinoma. 43,44 MAP1LC3C (microtubule-associated protein 1 light chain 3 gamma), a critical structural protein in autophagosome membrane, has been reported to be an independent prognostic biomarker in colorectal cancer. 45,46 However, there is little knowledge concerning prognostic implications of DAPK2, ITPR1, and MAP1LC3C in ESCC.…”
Section: Pca Analysis For High-risk and Low-risk Samples Based On M6a...mentioning
confidence: 99%
“…Thus, recent studies have profoundly explored the wide ranges from single gene marker to multigene array for the potential mRNA [ 7 , 8 ], long noncoding RNA (lncRNA) [ 9 ], and competing endogenous RNA (ceRNA) network [ 10 ]-based prognostic biomarkers for esophageal cancer. In addition to the genes, including FAM46A , RAB15 , SLC20A1 , IL1A , and ACSL1 , which have been found to be associated with the overall survival (OS) or relapse-free survival (RFS) of EAC patients [ 11 ], several autophagy-related genes [ 12 ], as well as glycolysis-related genes [ 13 ], have also been detected as the potential prognostic biomarkers of EAC progression. Moreover, ceRNA network-derived eight-gene panel [ 10 ] and four-gene panel [ 13 ] models have been established to predict the overall survival rate of EAC patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the genes, including FAM46A , RAB15 , SLC20A1 , IL1A , and ACSL1 , which have been found to be associated with the overall survival (OS) or relapse-free survival (RFS) of EAC patients [ 11 ], several autophagy-related genes [ 12 ], as well as glycolysis-related genes [ 13 ], have also been detected as the potential prognostic biomarkers of EAC progression. Moreover, ceRNA network-derived eight-gene panel [ 10 ] and four-gene panel [ 13 ] models have been established to predict the overall survival rate of EAC patients. Furthermore, several genetic panels have been developed based on the tumor microenvironment-associated oncogenes [ 14 , 15 ], flavoproteins [ 16 ], histone modifications [ 17 ], actin cytoskeletal proteins [ 18 ], and other heterogeneous pathways [ 19 21 ], to track the ESCC prognostic signatures.…”
Section: Introductionmentioning
confidence: 99%